Struktur Komunitas Diatom Epifit pada Pelepah Nypa Fruticans di Sekitar Pulau Cawan Kabupaten Indragiri Hilir Provinsi Riau - Arifin, Nur; Siregar, Sofyan Husein; Nurrachmi, Irvina (Jurnal Perikanan dan Kelautan, 2018)
Diatoms are the largest phytoplankton group and as the primary producer in marine waters. This research was conducted in September 2016 around Cawan Island of In-dragiri Hilir Regency of Riau Province. The aim of this research was to determine the structure of epiphytic diatom community on the midrib of Nypa fruticans and to deter-mine water quality as well as to see the relationship of epiphytic diatoms abundance with water quality. The survey method was applied in this research and sampling loca-tion determined by purposive sampling. Measurement of water quality was done by in situ and ex situ which consist of biology, physics and chemical parameters. Nitrate concentrations in waters ranged from 0,0139 to 0,0639 mg/l and phosphate concentra-tions ranged from 0,1342 to 0,2345 mg/l. The epiphytic diatoms on the midrib of Nypa fruticans in Cawan Island consist of 18 genera of diatoms, the average value of abun-dance ranged from 7.385 to 23.042 individual/cm2, the mean value of diversity index ranged from 1,41 to 2,05.The dominance index value ranged from 0,27 to 0,52 and the uniformity index value ranged from 0,58 to 0,91. Meanwhile, the correlation of diatom abundance with concentration of nitrate was 0,21 (weak relationship) and correlation of diatomic abundance with phosphate concentration was 0,11 (very weak relation-ship). Based on the result of epiphytic diatom calculation on the midrib of Nypa fruti-cans can be concluded that the waters in Cawan Island was in medium contaminated condition.